Measuring shared decision-making and collaborative goal setting in community rehabilitation: a focused ethnography using cross-sectional surveys in Canada - Karin Olson; Sunita Vohra; Tracy Wasylak; Katie Churchill; Peter Faris (BMJ Open)
Objective To describe and measure the shared decision-making (SDM) experience, including goal-setting experiences, from the perspective of patients and providers in diverse community-rehabilitation settings.Design Prospective, longitudinal surveys.Setting 13 primary level-of-care community-rehabilitation sites in diverse areas varying in geography, patient population and provider discipline341 adult, English-speaking patient-participants, and 66 provider-participants.Measures Alberta Shared decision-maKing Measurement Instrument (dyadic tool measuring SDM), WatLX (outpatient rehabilitation experience) and demographic questionnaire. Survey packages distributed at two timepoints (T0=recruitment; T1=3 months later).Results We found that among 341 patient–provider dyads, 26.4% agreed that the appointment at recruitment involved high-quality SDM. Patient perceptions of goal-setting suggested that 19.6% of patients did not set a goal for their care, and only 11.4% set goals in functional language that tied directly to an activity/role/responsibility that was meaningful to their life. Better SDM was clinically associated with higher total family income (p=0.045).Conclusions These findings provide evidence for the importance of SDM and goal setting in community rehabilitation. Among patients, lower ratings of SDM corresponded with less recognition of their preferences. Actionable strategies include supporting financially vulnerable patients in realising SDM through training of providers to make extra space for such patients to share their preferences and better preparing patients to articulate their preferences. We recommend more research into strategies that advance highly functional goal setting with patients, and that lessen survey ceiling effects.